Besides regular chromosome segregation and allied reproductive traits in Valeriana jatamansi Jones (Valerianoideae, Caprifoliaceae) – the gynodioecious species develops multiple evolutionary pathways as subsistence links. Issue 2 (3rd April 2017) - Rather, Aabid M.; Nawchoo, Irshad A.; Raina, R.
Abstract: This study has been carried out to assess and explore the sexual diversity in an important medicinal plant, Valeriana jatamansi . The species is gynodioecious and produces hermaphrodite and female flowered plants that grow sympatrically. It was observed that hermaphrodite and female flowered plants can be segregated only during the flowering phase. In addition to gynodioecy, the production of a sterile flower at each branching point (dichotomy) of inflorescence and the reduction in the length of peduncles in acropetal manner results in reduction of the angle of branches from first dichotomy to top of inflorescence, resulting in flagship effect. This crowding effect of flowers helps to attract pollinators and the fertilization of a flower by pollen from another flower on the same plant (known as geitonogamy) by means of staminal movement in hermaphrodite flowers. Female flowered plants did not set any seeds when isolated from bisexual flowered plants. Female seeds showed more seed viability (89.5%) than hermaphrodite ones (84.25%). The species also operates a unique mechanism of piercing of stamens through closed floral buds to facilitate cross pollination. Pollen/ovule ratio was in favor of Cruden's xenogamous nature. In all populations of Valeriana jatamansi, we observed 16 bivalents at metaphase-I indicating the chromosome number to be 2 n = 32 and normal meiosis without any abnormalities (e.g. laggards, bridges, and micronuclei). Valeriana jatamansi seed germination responded best to the nitrogenous compounds apart from scarification (85% with MGT 4.25 days), showing 80% in 1 mM of thiourea with MGT of 3.75 days. The paper discusses the multiple reproductive strategies employed by the species to increase its fitness and points out that the species follows unique pathways of evolution.